2003
DOI: 10.1074/jbc.c300180200
|View full text |Cite
|
Sign up to set email alerts
|

The β-Subunit of the Protein-conducting Channel of the Endoplasmic Reticulum Functions as the Guanine Nucleotide Exchange Factor for the β-Subunit of the Signal Recognition Particle Receptor

Abstract: Cotranslational protein transport to the endoplasmic reticulum is controlled by the concerted interaction of three GTPases: the SRP54 subunit of the signal recognition particle (SRP) and the ␣-and ␤-subunits of the SRP receptor (SR). SR␤ is related to ADP-ribosylation factor (ARF)-type GTPases, and the recently published crystal structure of SR␤-GTP in complex with the binding domain of SR␣ suggested that SR␤, like all ARF-type GTPases, requires a guanine nucleotide exchange factor (GEF) for function. Searchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…In the same study, those investigators showed that expression of a dominantnegative GEF of GBF1 (which can interact with ARF1) also led to dissolution of the trans-Golgi and ATP7A-containing compartments, although copper-responsive trafficking was lost. The Sec61␤ yeast homologs sbh1p and sbh2p were shown in a different study to function as GEFs, consistent with the observation that they contain homologous sec7 domains required for GEF function (Helmers et al, 2003). Our data suggest that Sec61␤ may function as a GEF and may modulate the ATP7A trans-Golgi compartment in a manner similar to that of the yeast GEF GBF1, possibly in concert with the ARF family of proteins.…”
Section: Discussionsupporting
confidence: 70%
“…In the same study, those investigators showed that expression of a dominantnegative GEF of GBF1 (which can interact with ARF1) also led to dissolution of the trans-Golgi and ATP7A-containing compartments, although copper-responsive trafficking was lost. The Sec61␤ yeast homologs sbh1p and sbh2p were shown in a different study to function as GEFs, consistent with the observation that they contain homologous sec7 domains required for GEF function (Helmers et al, 2003). Our data suggest that Sec61␤ may function as a GEF and may modulate the ATP7A trans-Golgi compartment in a manner similar to that of the yeast GEF GBF1, possibly in concert with the ARF family of proteins.…”
Section: Discussionsupporting
confidence: 70%
“…Sec61 has been copurified with Sec66 as part of a posttranslational translocation complex that includes Sec63 and Sec72 (34). Srp102 is part of the receptor complex for the signal recognition particle that targets ribosomes harboring secreted or membrane proteins to the Sec61 complex, and independent lines of evidence indicate it is closely associated with Sec61 components (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…5 and 6). Previously a segment in the Sbh1p cytosolic domain was shown to display homology with the Sec7 domain responsible for guanine nucleotide exchange activity for ADP-ribosylation factor family GTPases and it was shown that Sbh1p can act as a guanine nucleotide exchange factor for signal recognition particle receptor ␤ (14). The Sec61 ␤ subunit was also shown to interact with the large ribosomal subunit and was proposed to mediate ribosome docking with the Sec61 complex (13).…”
Section: Discussionmentioning
confidence: 99%
“…The ␤ subunit is not essential but has a facilitating role in translocation in mammalian cells (12). In addition to its interactions with Sec61p, the mammalian ␤ subunit has been shown to interact with signal peptidase (12), and the ribosome (13) and the yeast ␤ subunit, Sbh1p, was shown to act as a guanine nucleotide exchange factor for signal recognition particle receptor (14). The two yeast ␤ subunits, Sbh1p and Sbh2p (previously also called Seb1p and Seb2p), are encoded by non-essential genes.…”
mentioning
confidence: 99%